PEMBERDAYAAN GUGATAN SEDERHANA PERKARA PERDATA GUNA MEWUJUDKAN PENYELENGGARAAN PERADILAN BERDASARKAN ASAS SEDERHANA, CEPAT DAN BIAYA RINGAN - Benny Riyanto; Hapsari Tunjung Sekartaji (Faculty of Law, Universitas Diponegoro, 2019)
The usual legal system of civil law often require an expensive cost, a complicated and takes long time to complete a case. The demand to resolve small civil case through special legal system is increase. Gugatan sederhana (adopted from Small Claims Court) is an alternative legal system provided in the district court to settle the civil case that are more accessible and effective in maintaining legal rights for justice seekers. The empowerment of gugatan sederhana starts in the district court because it is the first level court to go to resolve the civil case faced by justice seekers.